Penerapan pertanian perkotaan untuk penguatan ketersediaan ruang terbuka hijau privat pada kota produksi penghasil minyak bumi di Duri Indonesia - Gendraya Rohaini; Sukendi Sukendi; Sofyan Husein Siregar; Dessy Yoswati (Jurnal Zona, 2021)
Ministry of National Development Planning (PPN) / National Development Planning Agency (Bappenas), the Republic of Indonesia stated that Indonesia is committed to the environment in 2045 with a program towards Indonesia's Green Economy marked by a 41% reduction in emissions. The existence of green open space (GOS) is an important factor in supporting the ecological sustainability of a city, The role of GOS in addition lies in improving temperature and humidity also found in the reduction of CO2 emissions. The main purpose of this research is to plan an integration strategy between GOS and the Urban Agriculture Program. in Duri City, Bengkalis Regency, Riau Province, which is one of the petroleum producing cities in Indonesia. The method of this research using GIS-AHP approach. The strategy action consists of environmental, economics and social  commitments are maintained for development sustainability by implementing green technology, green economic regulation and strengthening the green community movement. The main result of research prove that strategic integration of GOS Privat with Urban Agriculture Program u in Duri City contributes GOS Private availability of 14,134%, so that gos private has exceeded the requirement limit of at least 10% based on the mandate of the Spatial Arrangement Act, Republic of Indonesia.